Cultivating te ao Māori in mainstream school environments : empowering cultural responsiveness : a thesis presented in partial fulfilment of the requirements for the post-graduate degree of Master of Education in Māori Education at Massey University, Te Papa-i-oea, Manawatū, Aotearoa, New Zealand - Hasson, Jordyn (Massey University, 2026)
This thesis explores how kaiako in mainstream primary school settings across Aotearoa understand and enact culturally responsive practice grounded in te ao Māori. Situated within ongoing inequities experienced by Māori learners in the education system, this study examines the relational, cultural, and systemic conditions that influence the implementation of culturally responsive pedagogy. Guided by Kaupapa Māori theory and informed by culturally sustaining pedagogy, this research centres Māori worldviews, values, and aspirations as foundational to teaching and learning. Qualitative data were gathered through semi-structured interviews with eight kaiako working in mainstream primary schools. The research prioritised relational and culturally grounded approaches, including whakawhanaungatanga and participant validation, to uphold the mana of all contributors. Findings reveal five interconnected themes: the centrality of whanaungatanga in teaching practice; the normalisation of te reo Māori me ōna tikanga; the importance of fostering student agency and cultural identity; the impact of systemic barriers; and the ongoing reflective growth of kaiako. These findings demonstrate that culturally responsive practice is deeply relational and requires sustained commitment at both individual and systemic levels. This study contributes to the field of Māori education by providing insight into how culturally responsive pedagogy is enacted within mainstream schooling contexts. It highlights the ways in which kaiako can support Māori learners to experience education as affirming, empowering, and reflective of their identity as Māori, while also offering practical implications for teachers, schools, and the wider education system.
Māori Masters Thesis
Keywords: 390304 Primary education; 390407 Inclusive education; 450811 Te mātauranga Māori i roto i te mātauranga (Mātauranga Māori in education)